The future of psychiatry - Norman Sartorius (Eco-Vector, 2021)
Since the Second World War mental health programmes and psychiatry have made significant advances. Countries, as well as the United Nations, have recognized the magnitude and severity of mental health problems, and numerous national programmes have been launched to deal with them. Technology relating to the treatment of mental disorders has advanced and significant progress has been made in terms of knowledge regarding the functioning of the brain. The awareness of the need to protect the human rights of those with mental illness has increased. National and regional programmes against stigma and the consequent discrimination of those with mental illness, have been launched in many countries. Associations bringing together those who have experienced mental illness and their relatives, have come into existence in many countries.